First record of the genus Conilepia Hampson (Lepidoptera: Erebidae: Arctiinae) from India with the description of a new species. Issue 2 (26th November 2013) - Kirti, Jagbir Singh; Singh, Navneet; Joshi, Rahul
Abstract A new species, Conilepia hunliensis sp. n., is described from India. The new species is reported from Hunli (Arunachal Pradesh), which represents the first record of genus from India. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)